Serum homocysteine levels in patients with acute myocardial infarction - Alam, N; Chowdhury, AW; Hossain, MZ; Khondoker, MAH; Mallik, MU; Amin, MR; Hasan, GMS (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13234 J. Dhaka Med. Coll. 2012; 21(1): 23-27